A COMMUNICATIVE VIEW OF THE RIGHTFUL PLACE OF NONVERBAL COMMUNICATION IN NATIVE- AND FOREIGNLANGUAGE TEACHING - Brosnahan, Leger (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Nonverbal communication, an essential component of all languages, has been, for a number of historical reasons, almost completely neglected in the teaching of both native and foreign languages. Speech has often been added to reading and writing as proper goals of language teaching, but the need for knowing nonverbal communication if one is speaking face-to-face with another is only slowly being realized. What is needed are two-language, detailed, descriptive contrasts of the nonverbal communication of the native and the target dialects or languages. No such contrast is currently more needed than one contrasting the nonverbal-communication systems of Standard Spanish and Standard American English.